The influence of trust and social norms on the utilization of health service access in pregnant women - Sunarsih, Tri; Astuti, Endah Puji; Shanti, Elvika Fit Ari (MEDIA ILMU KESEHATAN, 2025)
Background: Maternal health is a crucial aspect of pregnancy, requiring adequate healthcare access to ensure the well-being of both mother and fetus. However, various social, cultural, and economic factors influence healthcare utilization among pregnant women.Objective: This study aims to analyze the impact of trust and social norms on healthcare access among pregnant women in Ngalang, Gedangsari, Gunungkidul.Methods: A quantitative approach was employed using multiple regression analysis, with healthcare access as the dependent variable and trust and social norms as independent variables. Data were collected from mothers with young children (0–6 years) through a structured questionnaire. Descriptive statistics and classical assumption tests were conducted to ensure data validity.Results: The results indicate that most respondents (76.3%) have high levels of trust and adherence to social norms, which significantly influence their utilization of healthcare services. The regression analysis shows a positive and significant relationship between trust, social norms, and healthcare access, with a determination coefficient (R²) of 19.4%.Conclusion: This suggests that while trust and social norms contribute to healthcare utilization, other factors also play a role. Additionally, traditional beliefs and limited health literacy may hinder healthcare access despite high trust levels.